Respuesta :
If you would like to know which statement is true about the solution to the set of equations, you can calculate this using the following steps:
x + y = 2 ... y = 2 - x
2x + y = 4
_________________
2x + (2 - x) = 4
2x - x = 4 - 2
x = 2
y = 2 - x = 2 - 2 = 0
(x, y) = (2, 0)
The correct result would be: There is one solution.
x + y = 2 ... y = 2 - x
2x + y = 4
_________________
2x + (2 - x) = 4
2x - x = 4 - 2
x = 2
y = 2 - x = 2 - 2 = 0
(x, y) = (2, 0)
The correct result would be: There is one solution.